Protection of liposomes by ferric salts against the UV damage and its implications for the origin of life - Turner, Ben; Wu, Kevin; Fiksel, Gennady; Subbotin, Vladimir (Frontiers in Astronomy and Space Sciences, 2025)
Previously, we presented a hypothesis on the Darwinian evolution of liposomes that relies only on natural and ever-present phenomena: solar UV radiation, day/night cycle, gravity, and the formation/release of amphiphiles in aqueous media. The new hypothesis comprises the necessary prerequisites for Darwinian evolution: adaptive traits and selective forces. The hypothesis suggests that amphiphilic molecules, introduced in the Archean water, inevitably form the Langmuir layer, bilayer, and liposomes at the water-air interface. The solar UV radiation could destroy the liposomes unless they acquire a crucial adaptive trait–the heavy content that sinks them to the bottom of the pool and facilitates protection from UV. The hypothesis makes two testable predictions: 1) ferric salts of Archean waters attenuate the UV, and 2) the attenuation protects the liposomes from solar UV destruction. The assumption of UV attenuation by ferric salt solutions has been tested by confirming that two salts, iron trichloride and ferric ammonium citrate, possess strong UV attenuation, reducing the UV intensity by a factor of 1,000 at a submersion depth of 6.3 mm and 7.4 mm, respectively. In the present study, we have tested the second conjecture by demonstrating that 10 mm of solutions, the ferric ammonium citrate or iron trichloride, completely protect UV-sensitive liposomes from UV damage. These results reinforce the proposed hypothesis and suggest that the Sun UV radiation and gravity could be the major selection forces for the abiogenesis.